Competência em informação para pesquisa científica de estudantes de cursos tecnológicos do Instituto Federal de Educação, Ciência e Tecnologia de São Paulo - IFSP - Dupin, Aline Aparecida da Silva Quintã (2018)
Information Literacy is an important requirement for individuals to be able to interact in this environment of continuous changes and accumulation of information to build knowledge. The objective of this work is to investigate how academic research is established regarding the Information Literacy of students of Instituto Federal de Educação, Ciência e Tecnologia de São Paulo (IFSP). To this end, monographs were selected for public access in the home pages of the campuses, which resulted in a sample of 96 completion work. This research is characterized as qualitative-quantitative and has a descriptive and exploratory character. In addition to the literature review and literature review, analyzes were carried out in the monographs and in the Curricular Matrices and Political Pedagogical Projects of the selected courses. Finally, the home pages of the IFSP campus libraries were analyzed in order to identify the informational resources made available by the libraries to their users and to verify if there were any training and guidance in the construction of scientific research. The results obtained after the analysis of the monographies were satisfactory, demonstrating that the students are attentive to the methodological delineations for the construction of an academic work. The analysis of the curricular matrices and the Political Pedagogical Projects showed that there are no specific disciplines for the development of Information Literacy, but there are disciplines that work the necessary skills to develop this competence. With regard to libraries, it was concluded that there are isolated actions for the development of Information Literacy in libraries of the IFSP network. With the results obtained, it is inferred that the students have the necessary tools and knowledge for the development of Information Literacy and that the IFSP has supported and sought to strengthen this competence.